Study of fluorine losses in oxyfluoride glasses - Bueno, L. A.; Messaddeq, Younes [UNESP]; Dias, F. A.; Ribeiro, SJL (Elsevier B.V., 2005)
Glasses in PbGeO3-PbF-CdF2 and GeO2-PbO-PbF2-CdF2 systems were studied and the fluorine losses during synthesis were investigated. Samples were characterized by differential scanning calorimetry (DSC), X-ray diffraction, Fourier transform infrared spectroscopy (FTIR) and Raman scattering spectroscopy. The use of stoichiometric germanate glass, PbGeO3, instead of introducing individual oxides (GeO2 + PbO) lead to decreasing fluorine losses, as detected by a fluorine ion selective electrode. The main structural features obtained from vibrational spectroscopy could be described by a metagermanate basic structure permeating fluorine rich regions. (c) 2005 Elsevier B.V. All rights reserved.